Zakat Administration in Islamic Economics Thought: Sharīʿah and Organisational Foundations and Contemporary Models - HOUHOU, Souad; HOUHOU, Hassina (Journal of Ecohumanism, 2026)
Zakat constitutes one of the fundamental pillars of the Islamic economic system owing to its pivotal role in achieving social solidarity, redistributing income, and alleviating poverty. However, the realisation of its Sharīʿah and economic objectives remains contingent on a practical administrative and institutional framework that ensures the proper collection and distribution of zakat in accordance with Sharīʿah regulations and the principles of good governance. This study seeks to elucidate the theoretical framework governing zakat administration within Islamic economic thought by analysing the Sharīʿah and organisational foundations that underpin the assignment of zakat affairs to the state and by clarifying the state's institutional role in overseeing this obligation. This study also aims to review and analyse contemporary administrative models of zakat management, whether based on voluntary or compulsory approaches, by explaining the mechanisms of zakat collection and distribution adopted in each model and highlighting their respective advantages and limitations in terms of effectiveness. The research adopts a descriptive–analytical methodology, drawing on relevant contemporary juristic and economic literature. The study concludes that the success of zakat administration in the modern era requires the adoption of an independent administrative system, a clear institutional structure, and adequate Sharīʿah supervision, alongside the utilisation of modern technologies and digitalisation to enhance transparency and efficiency. The findings further emphasise that unifying the organisational vision and integrating roles between the state and zakat institutions constitute a fundamental prerequisite for activating the developmental role of zakat and achieving its social and economic objectives.